Disparity in Relation to Covid-19 Preventive Behaviour and Associated Myths among Rural and Urban Residents of Lucknow: A Community Based Study - Shukla, Vinita; Kaushik, Amit; Sachan, Beena; Singh, Arvind Kumar; Kumari, Rashmi; Kandpal, Sunil Dutt; Jauhari, Sugandha (Indian Journal of Community Health, 2022)
Introduction: For curbing Covid-19 disease, adequate knowledge, attitude, and practices of both rural and urban population for Covid-19 disease prevention is required along with busting of the associated myths. Objectives: To assess the Knowledge, Attitude and Practices of urban and rural residents of Lucknow district regarding covid-19 preventive behaviour and associated myths. Methodology: A community-based study was conducted among 420 rural and 421 urban residents of Lucknow. Multistage random sampling was done to select the study subjects. A pre-designed pretested semi-structured questionnaire was used to collect the information regarding the Knowledge, Attitude and Practices of the residents for covid-19 disease causes, prevention, and treatment. Further, KAP scoring was done to compare the two groups. Results: The mean age of the rural and urban residents was 31.48 ± 12.05 and 30.93 ± 11.96 years respectively. Only 40.4 % urban and 25.5 % rural people had correct knowledge about social distancing (p<0.0001). Knowledge regarding quarantine for covid-19 disease prevention was less among the urban residents (64.6%) as compared to rural (70.5%) (p=0.035). More than one-third (37.6%) of the rural resident believed in the myth that alcohol can prevent the covid-19 disease (p=0.003). 68.8 and 70.5 percent rural and urban residents had positive attitude towards the Indian government’ efforts in curbing the disease. Majority of the urban (90%) and rural (87.6%) residents wore mask when they went out. Only one-fourth of the urban (24.7%) and rural (22.9%) had correct practices for the duration of hand washing. Conclusion: The knowledge was more among the urban people, attitude and practices were almost similar among both the rural and urban residents while myths were more observed among the rural residents.